Ferric chloride aided peracetic acid pretreatment for effective utilization of sugarcane bagasse - Zhuang, Jingshun; Kim, Kwang Ho; Jia, Linjing; Meng, Xianzhi; Kumar, Deepak; Leem, Gyu; Kang, Sung Bong; Li, Youming; Ragauskas, Arthur J.; Hou, Yi; Yoo, Chang Geun (Elsevier BV, 2022)
The synergetic impacts of ferric chloride aided peracetic acid (FPA) pretreatment were investigated to enhance the total biomass utilization through effective cellulose conversion and high-quality lignin production. The sugarcane bagasse pretreatment with 2% peracetic acid (PAA) and 0.1 mol/L ferric chloride (FeCl3) effectively removed 57.3% of lignin and 72.2% of xylan while preserving ∼ 97% of cellulose from sugarcane bagasse under mild temperature (90 °C). The FPA pretreated sugarcane bagasse was effectively hydrolyzed with a glucose yield of 313.0 mg/g-biomass, which was 4.5 times higher than the yield of untreated biomass (69.75 mg/g-biomass) and 1.6 and 3.6 times higher than that of individual PAA and FeCl3 pretreated sugarcane bagasse, respectively. The regenerated lignin (FPA lignin) showed great potential for further valorization by preserving the major interunit linkage (up to 86% of β-O-4) without significant carbohydrate contamination and lignin condensation due to its mild reaction conditions. In this study, the combination of PAA and FeCl3 synergistically enhanced the pretreatment efficiency on sugarcane bagasse and resulted in high fermentable sugar and high-quality lignin production. ？ 2022 Elsevier Ltd